Malaysian oil palm plantation sector: exploiting renewable energy toward sustainability production - Ahmad Ludin, Norasikin; M. Bakri, M. Azwan; Kamaruddin, Norman; Sopian, Kamaruzzaman; Deraman, Mohd Solah; Hamid, Norul Hisham; Asim, Nilofar; Othman, Mohd Yusuf (Elsevier, 2014)
The Malaysian palm oil industry spans the entire value chain from upstream processes to downstream activities. This paper aims to review the progress of the palm oil industry and the current issues in the plantation sector, such as labor shortage, sustainable production, and greenhouse gas emission from the cultivation process. Palm oil cultivation is known for its labor-intensive process. Foreign laborers are usually employed in Malaysian palm oil plantations for harvesting, fruit collecting, and general maintenance works. Some issues have affected the supply of workers to Malaysian palm oil plantations. Farm mechanization, which has always been recommended as a tool to reduce dependency on foreign workers, is expected to solve the issues. However, certain considerations should be investigated, such as fuel consumption, to reduce its impacts on the environment. The currently available farm machineries that are frequently used contribute to almost 211 million kg of CO2-eq per year, as diesel consumption stands at 290 million L per year. Therefore, this paper also examines the potential renewable energy resources for the palm oil cultivation process. Exploiting renewable energy technologies in plantation operations, such as battery-powered electric vehicles charged using a solar photovoltaic (PV) system, can reduce up to 750 tonnes of CO2-eq per year. Therefore, this initiative will increase the sustainability of the Malaysian palm oil industry in general.